Trends in lung cancer survival in the Nordic countries 1990–2016 : The NORDCAN survival studies - Lundberg, Frida E.; Ekman, Simon; Johansson, Anna L.V.; Engholm, Gerda; Birgisson, Helgi; Ólafsdóttir, Elínborg J.; Mørch, Lina Steinrud; Johannesen, Tom Børge; Andersson, Therese M.L.; Pettersson, David; Seppä, Karri; Virtanen, Anni; et al. (ELSEVIER IRELAND LTD, 2024)
Objectives: The aim of this study was to evaluate if the previously reported improvements in lung cancer survival were consistent across age at diagnosis and by lung cancer subtypes. Materials and methods: Data on lung cancers diagnosed between 1990 and 2016 in Denmark, Finland, Iceland, Norway and Sweden were obtained from the NORDCAN database. Flexible parametric models were used to estimate age-standardized and age-specific relative survival by sex, as well as reference-adjusted crude probabilities of death and life-years lost. Age-standardised survival was also estimated by the three major subtypes; adenocarcincoma, squamous cell and small-cell carcinoma. Results: Both 1- and 5-year relative survival improved continuously in all countries. The pattern of improvement was similar across age groups and by subtype. The largest improvements in survival were seen in Denmark, while improvements were comparatively smaller in Finland. In the most recent period, age-standardised estimates of 5-year relative survival ranged from 13% to 26% and the 5-year crude probability of death due to lung cancer ranged from 73% to 85%. Across all Nordic countries, survival decreased with age, and was lower in men and for small-cell carcinoma. Conclusion: Lung cancer survival has improved substantially since 1990, in both women and men and across age. The improvements were seen in all major subtypes. However, lung cancer survival remains poor, with three out of four patients dying from their lung cancer within five years of diagnosis. Peer reviewed